Did Two Zlatousts from the Collection of the Princes Chartoryski Library in Cracow Once Belong to Fr Iwan Wiszeński? - Stradomski, Jan (Poznańskie Studia Slawistyczne, 2018)
In the collection of manuscripts of the Princes Chartoryski Library in Cracow, there are two manuscripts (from the beginning of the 17th century) which are related, in academic literature, with the person of Orthodox monk, Iwan Wiszeński. The volumes, described in catalogues as Zlatousts, were to be brought by him directly from the Mt Athos. Codicological and textual analysis of the manuscripts shows that the tomes are not the Zlatousts, but two volumes (Lent and Paschal period) from an extensive collection of Byzantine and Slavic panegyrical works, known as Studios Monastery Homiliarium. Characteristic features of both the books show that the manuscripts were written on the area of the former Polish Republic (The Polish-Lithuanian Commonwealth), thus they may only be copies of the originals brought from the Balkan region (not necessarily the Mt Athos). It is possible that Iwan Wiszeński was engaged personally in the delivery of manuscripts of this type, unpopular in Orthodox literature in the Ruthenian territory, but not of these particular ones.